Frecuencia de fasciola hepática en ganado vacuno en fincas del municipio de Silvia – Cauca (2022)
The Fasciola hepatica is a parasite from the class Trematoda of the order Digenea, which maintains a wide distribution worldwide. The grass contaminated with feces is the main source of transmission, with snails acting as an essential part of the biological cycle. The lesions mainly are presents in the liver and the clinical symptomatology is mainly gastrointestinal secondary to hepatic affection. The diagnosis can be parasitological from flotation or sedimentation methods, immunological with tests such as ELISA and necropsy based on anatomopathological findings. Prevention is based on the control of the intermediate host, leaving in second place the pharmacological treatment of the animals. The objective of the present study was to determine the frequency of Fasciola hepatica in cattle in the municipality of Silvia-Cauca through a coproparasitological examination. 60 fecal samples were taken during the dry season (June to October 2021) and analyzed using the modified Dennis test. Frequencies 15% were found. The variables species, sex and age did not constitute risk factors for distomatosis; however, the infection rate increased as the altitude above sea level increased (p<0.01), making the area of origin a risk factor for the disease.